2020
DOI: 10.2196/22326
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Multimodal Pain Program With Telephone Support for Adults With Chronic Temporomandibular Disorder Pain: Randomized Controlled Pilot Trial

Abstract: Background Chronic pain from temporomandibular disorders remains an undertreated condition with debate regarding the most effective treatment modalities. Objective The aim of the study was to investigate the treatment effect of an internet-based multimodal pain program on chronic temporomandibular disorder pain and evaluate the feasibility of a larger randomized controlled trial. Methods An unblinded randomi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 40 publications
0
25
0
1
Order By: Relevance
“…After screening, 83 articles were rejected as they did not meet the inclusion criteria for several reasons leaving 84 papers whose full text was obtained and read. After examining the full text of these 84 papers, 20 papers (19 original studies and one follow‐up report) were identified as eligible for inclusion in this systematic review: Komiyama et al, 1999 16 ; Wright et al, 2000 17 ; Carlson et al, 2001 3 ; Dworkin et al, 2002 18 ; Michelotti et al, 2004 19 ;Truelove et al, 2006 4 ; Turner et al, 2006 20 ; Mulet et al, 2007 21 ; Turner et al, 2011 22 ; Nie‐mela et al, 2012 23 ; Michelotti et al, 2012 24 ; Craane et al, 2012 25 ; De Vocht et al, 2013 26 ; Conti et al, 2015 27 ; Costa et al, 2015 28 ; Qvintus et al, 2015 29 ; Giro et al, 2016 30 ; Lam et al, 2020 31 ; De Resende et al, 2021 32 ; Peixoto et al, 2021 33 . A list of the 64 papers excluded with reasons for exclusion is available in the Appendix S3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening, 83 articles were rejected as they did not meet the inclusion criteria for several reasons leaving 84 papers whose full text was obtained and read. After examining the full text of these 84 papers, 20 papers (19 original studies and one follow‐up report) were identified as eligible for inclusion in this systematic review: Komiyama et al, 1999 16 ; Wright et al, 2000 17 ; Carlson et al, 2001 3 ; Dworkin et al, 2002 18 ; Michelotti et al, 2004 19 ;Truelove et al, 2006 4 ; Turner et al, 2006 20 ; Mulet et al, 2007 21 ; Turner et al, 2011 22 ; Nie‐mela et al, 2012 23 ; Michelotti et al, 2012 24 ; Craane et al, 2012 25 ; De Vocht et al, 2013 26 ; Conti et al, 2015 27 ; Costa et al, 2015 28 ; Qvintus et al, 2015 29 ; Giro et al, 2016 30 ; Lam et al, 2020 31 ; De Resende et al, 2021 32 ; Peixoto et al, 2021 33 . A list of the 64 papers excluded with reasons for exclusion is available in the Appendix S3.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen of the studies used pain intensity as an outcome measure and it was measured using: the visual analogue scale (VAS) in nine studies 3,16,19,23–25,27,32,33 ; the characteristic pain intensity scale (CPI) in three studies 18,20,22 ; a numerical rating scale (NRS) in two studies 21,26 ; the symptom severity index (SSI) in one study 17 ; and the graded chronic pain scale (GCPS) in one study 31 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method of delivery can also increase self-efficacy and has shown sustainability at follow up (Marsch et al, 2007;Smith et al, 2019). Online pain management has been successfully used in temporomandibular disorder pain (Lam et al, 2020), in veteran population (Higgins et al, 2020), for people with low back pain (Du et al, 2017). Although newer and less well-studied, an online relapse prevention program for adolescents was deemed to be both feasible and acceptable (Sanchez & Bartel, 2015), and efficacy was demonstrated for a computer-based SUD intervention (Marsch et al, 2007).…”
Section: Online and Virtual Pain And Sud Interventionsmentioning
confidence: 99%
“…There are still disagreements over the most effective and cost-effective treatment approach that can be widely distributed and used [20]. It is based on the clinical experience that, as the teeth are the most important components of the masticatory system and as they have a close relationship with the temporomandibular joint and masticatory muscles, any change to their normal functioning can induce pathological changes in the temporomandibular joint.…”
Section: Introductionmentioning
confidence: 99%